2008
DOI: 10.1002/da.20331
|View full text |Cite
|
Sign up to set email alerts
|

Do mood disorders alter crying? a pilot investigation

Abstract: Clinical commentators widely interpret crying as a sign of depressed mood. However, there is virtually no empirical data on this topic, and the evidence that mood disorders alter crying is surprisingly weak. This study compared mood disordered patients to a nonpsychiatric reference group on the frequency, antecedents, and consequences of crying behavior using a well-validated questionnaire measure of crying. Forty-four outpatients diagnosed with three forms of mood pathology were age and gender matched to a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Finally, the cathartic nature of crying may also have potential clinical implications for emotional disorders suggesting a need to examine cathartic effects in clinical samples. Depression is associated with more frequent crying, but some research suggests more severe depression is associated with an inability to cry (e.g., vingerhoets, Rottenberg, Cevaal, & Nelson, 2007;Rottenberg, Gross, Wilhelm, Najmi, & Gotlib, 2002) and less experience of mood improvement after crying (Rottenberg, Cevaal, & vingerhoets, 2008). Thus, future research would be well served by examining the situational factors that determine catharsis in clinical populations.…”
Section: Discussionmentioning
confidence: 95%
“…Finally, the cathartic nature of crying may also have potential clinical implications for emotional disorders suggesting a need to examine cathartic effects in clinical samples. Depression is associated with more frequent crying, but some research suggests more severe depression is associated with an inability to cry (e.g., vingerhoets, Rottenberg, Cevaal, & Nelson, 2007;Rottenberg, Gross, Wilhelm, Najmi, & Gotlib, 2002) and less experience of mood improvement after crying (Rottenberg, Cevaal, & vingerhoets, 2008). Thus, future research would be well served by examining the situational factors that determine catharsis in clinical populations.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, it should also be noted with regard to crying symptoms that there are surprisingly few empirical data supporting a relationship between frequent or labile crying and depression, despite the common (and reasonable) assumption by clinicians that such an association exists [63][66]. Indeed, the DSM-IV criteria for diagnosis of major depression do not require changes in either the threshold or intensity of the crying response [64], which are defining indicators of PBA.…”
Section: Discussionmentioning
confidence: 99%
“…There was also little empirical support for the competing claim that severely depressed individuals lose their capacity to cry. On the one hand, Rottenberg, Gross, Wilhelm, Najmi and Gotlib (2002) failed to demonstrate that depressed patients were more likely to cry when being exposed to a sad movie; but on the other hand, Rottenberg, Cevaal and Vingerhoets (2008), using validated crying measures, showed that (compared with the reference group) patients with mood pathology reported increased cry proneness to negative antecedents, but no differences were found with respect to crying proneness to positive antecedents. Patients additionally reported less mood improvement after crying than did controls.…”
Section: Crying and Psychological Healthmentioning
confidence: 99%